E-Catalog System Quality and Its Impact on Behavioral Intention: The Mediating Role of Perceived Ease of Use and Perceived Usefulness - Muslichah, Muslichah; Fatimah, Fatimah (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2026)
E-catalog systems have become essential tools in the digital age, revolutionizing the way companies and organizations show their goods and services to consumers. This study investigates the direct and indirect effect of e-catalog system quality (ESQ) on behavioral intention (BI) with perceived ease of use (PEOU) and perceived usefulness (PU) as intervening variables. Based on a sample of 75 respondents, the results indicated that ESQ has a significant positive effect on BI, ESQ has a significant positive impact on PU and PEOU, PU and PEOU have a significant positive effect on BI, PU and PEOU mediate the relationship between ESQ and BI. This study adds to the theoretical frameworks of technology acceptance by offering insights unique to the governmental domain. Practical contributions encompass guiding government agencies in enhancing their e-catalog offerings. The study offers actionable insights for optimizing system design, user interfaces, and functionality, with the aim of improving user experiences and fostering higher adoption rates.